Implementasi Flipped Classroom Berpendekatan Deep Learning untuk Meningkatkan Kemampuan Berpikir Kritis dan Kolaborasi Murid Fase F XI - Ayu Febriasari; Jodion Siburian; Ali Sadikin (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study aims to analyze the effect of the implementation of the Flipped Classroom model with a Deep Learning approach on the critical thinking and collaboration skills of Phase F XI students on the digestive system material. The study used a mixed methods with an embedded experimental design type. The research sample consisted of one experimental class that received Flipped Classroom learning with a Deep Learning approach and one control class that received Problem Based Learning (PBL) learning. Data on critical thinking skills were collected through essay tests, while collaboration skills were obtained through observation sheets. Quantitative data analysis used One-Way MANCOVA and qualitative analysis was carried out through data reduction, data presentation, and drawing conclusions assisted by NVivo. The results showed a simultaneous significant effect between the learning model on students' critical thinking and collaboration skills after controlling for initial abilities with a significance value of 0.002 (p<0.05). The average posttest critical thinking of the experimental group was 71.69 higher than the control group at 62.53. Meanwhile, the collaboration skills of both groups showed a relatively balanced increase. The ANCOVA results showed that the Flipped Classroom model with a Deep Learning approach significantly impacted critical thinking skills, but did not show a significant difference in collaboration skills. The research findings indicate that the integration of Flipped Classroom and Deep Learning is effective in improving students' critical thinking skills and supporting 21st-century learning.